Love - Doyle, Roddy 1958- (Viking, 2020)
"Two old friends reconnect in Dublin for a dramatic, revealing evening of drinking and storytelling in this winning new novel from the author of the Booker Prize winning Paddy Clarke Ha Ha Ha Davy and Joe were drinking pals back in their Dublin youth. Davy rarely sees Joe for a pint anymore--maybe one or two when Davy comes over from England to check on his elderly father. But tonight Davy's father is dying in the hospice, and Joe has a secret that will lead the two on a bender back to the haunts of their youth. Joe had left his wife and family a year earlier for another woman, Jessica. Davy knows her too, or should--she was the girl of their dreams four decades earlier, the girl with the cello in George's pub. As Joe's story unfolds across Dublin--pint after pint, pub after pub--so too do the memories of what eventually drove Davy from Ireland: the upheaval that Faye, his feisty, profane wife, would bring into his life; his father's somber disapproval; the pained spaces left behind when a parent dies. As much a hymn to the Dublin of old as a delightfully comic yet moving portrait of what it means to try to put into words the many forms that love can take, Love marks a triumphant new turn for Roddy Doyle"--
Keywords: Male friendship / Fiction; Secrecy / Fiction; Reminiscing / Fiction; Dublin (Ireland) / Fiction; FICTION / Family Life; FICTION / Friendship; FICTION / Literary; Male friendship; Reminiscing; Secrecy; Ireland / Dublin; Friendship / Fiction; Humorous fiction; Romance fiction; Fiction; Fiktionale Darstellung